ELECTROCHEMICAL REDUCTION OF IONS IN METALS/ALLOYS AT A LIQUID CATHODE VERSUS A SOLID CHEMICALLY IDENTICAL ONE - OLEG B. GIRIN; DMYTRO G. KOROLYANCHUK (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The purpose of this work was further experimental verification of the existence of the phenomenon of electrochemical phase formation in metals and alloys via a supercooled liquid state stage. It was assumed that replacing a solid cathode with a chemically identical liquid one would lead to higher electrochemical reduction rates of ions of the electrodepositing metal/alloy. The experimentation involved a cathode of Wood’s alloy having melting point at 68.5 °С. The electrocrystallization of some metals (Ni, Co, Fe) and alloys (Fe-Сr, Fe-Сr-Ni) was carried out at 65 °C with a solid cathode and at 75 °C with a liquid one. The experimentation revealed the anticipated electrochemical features of the interface between a cathode in its predetermined state of aggregation and the electrodepositing metal or alloy in full measure. It was concluded that the phenomenon of electrochemical phase formation in metals and alloys via supercooled liquid state stage is proved by the deionization acceleration in electrodepositing metals and alloys on replacing a solid cathode with a chemically identical liquid one.